The Effectiveness of Using Youtube Applications as Learning Media to Increase Reading and Writing Interest of Elementary School Students’ - Nafilah, Nahla Putri; Sakti, Asri Wibawa (ASEAN Journal of Educational Research and Technology, 2022)
The Education Era 4.0 has demanded students' to improve their literacy skills, especially elementary school Students'. The purpose of this study was to determine the effectiveness of the use of the Youtube application as a learning medium to improve children's literacy skills. Unfortunately, until now there has been no research that discusses the Effectiveness of Using Youtube Applications as Learning Media to Increase the Reading and Writing Interests of Elementary School Students'. The research method used is a qualitative descriptive approach which is carried out through field research and interviews. In addition, we also conducted a literature study related to previous relevant research studies. Based on the results of the study, there was an increase in student learning outcomes by using Youtube as a learning medium. This shows that the presentation of creative learning materials can stimulate Students' interest and motivation which will have an impact on increasing Students' literacy skills. It can be concluded that the Youtube application has proven to be effective in presenting interesting learning videos so that it can increase the interest and literacy skills of elementary school Students'. This literacy and literacy ability will later be very useful for elementary school students' as a provision to support Students' in the 4.0 Education Era for a better future.